Термодинамічний аналіз формування енергетичного оптимуму газифікації вугілля - Тутова, Олена Валеріївна; Пінчук, Валерія Олександрівна (Український державний університет науки і технологій, ННІ «Дніпровський металургійний інститут», ІВК ≪Системні технології≫, Дніпро, 2026)
UKR: У роботі застосовано рівноважне термодинамічне моделювання для аналізу енергетичної ефективності газифікації вугілля залежно від коефіцієнта витрати окисника. Коефіцієнт витрати окисника розглядається як неперервний керувальний параметр, а аналіз ґрунтується на узгодженому дослідженні рівноважної температури процесу, складу, теплоти згоряння та питомого виходу генераторного газу. Встановлено, що реакція зазначених параметрів на зміну коефіцієнта витрати окисника має стійку тристадійну структуру, яка включає область неповного перетворення, оптимальну область та область надлишкового окислення. Показано, що зміна коефіцієнта витрати окисника призводить до узгодженої трансформації складу газу, зокрема до максимуму сумарної горючої складової та мінімуму продуктів окислення при значенні близько 0,3. Показано, що температура процесу зростає монотонно зі збільшенням коефіцієнта витрати окисника і не визначає положення енергетичного оптимуму, зростання температури та виходу газу після певного значення коефіцієнта витрати окисника вже не компенсує зниження його теплоти згоряння. Запропоновано інтегральний енергетичний показник, який враховує одночасно вихід газу та його теплоту згоряння. Встановлено, що цей показник має чіткий максимум при коефіцієнті витрати окисника близько 0,3 для всіх досліджених умов. Отримані результати дозволяють розглядати зазначене значення як універсальну характеристичну точку процесу газифікації, що визначається його внутрішньою термодинамічною структурою та відповідає області раціональних режимів із мінімальними окислювальними втратами.

ENG: Equilibrium thermodynamic modeling was applied to analyze the energy efficiency of coal gasification as a function of the oxidizer consumption coefficient. The oxidizer consumption coefficient is considered as a continuous control parameter that determines the balance between reduction and oxidation processes, and the analysis is based on the coordinated evaluation of equilibrium temperature, producer gas composition, its heating value, and specific gas yield. It is shown that variation of the oxidizer consumption coefficient leads not to isolated changes of individual parameters, but to their interrelated transformation with a clearly pronounced structural character. It is established that within the studied range, a three-stage structure of the process is formed, including a region of incomplete conversion with the presence of unreacted carbon, a region of rational operating conditions, and a region of excessive oxidation accompanied by a decrease in the content of combustible gas components. It is shown that transitions between these regions are characterized by changes in the behavior of the main parameter dependencies, reflecting a shift in the balance between dominant thermochemical processes. It is established that within the region of rational operating conditions, an energy-optimal gasification regime is formed, corresponding to the maximum of the total combustible fraction of the producer gas and the minimum of oxidation products. It is shown that this regime is realized at an oxidizer consumption coefficient of approximately 0.3 and corresponds to the region of minimal oxidation losses. The introduction of the logarithmic indicator lg((CO+H₂)/CO₂) made it possible to obtain a stable criterion for evaluating the gasification regime, ensuring unambiguous identification of the optimum region. It is shown that the maximum of this indicator coincides with the maximum of the total combustible fraction and the minimum of oxidation products, confirming the realization of an optimal reduction–oxidation balance. It is established that the gasification temperature increases monotonically with increasing oxidizer consumption coefficient and does not determine the position of the energy optimum. It is shown that beyond a certain value of the oxidizer consumption coefficient, further increases in temperature and gas yield no longer compensate for the decrease in gas heating value, resulting in reduced energy efficiency. To generalize the obtained results, an integral energy indicator was proposed, which simultaneously accounts for the producer gas yield and its heating value. It is established that this indicator exhibits a well-defined maximum at an oxidizer consumption coefficient of approximately 0.3 for all investigated conditions, despite the opposite trends of its components. The obtained results show that the energy optimum of the gasification process is formed as a result of coordinated variation of process parameters and is determined by its internal thermodynamic structure. This makes it possible to move from the analysis of individual characteristics to a system-based identification of the rational gasification regime corresponding to minimal oxidation losses and maximum total energy output of the producer gas.
Thermodynamic Analysis of Energy Optimum Formation in Coal Gasification
О. Тутова: ORCID 0000-0001-6846-0327; В. Пінчук: ORCID 0000-0001-7684-1867
Keywords: газифікація; вугілля; термодинамічний аналіз; коефіцієнт витрати окисника; генераторний газ; енергетичний оптимум; інтегральний енергетичний показник; gasification; coal; thermodynamic analysis; oxidizer consumption coefficient; producer gas; energy optimum; integral energy indicator; КЕСЕ; TECHNOLOGY